2014
DOI: 10.3109/13880209.2013.863949
|View full text |Cite
|
Sign up to set email alerts
|

Habb-e-Asgand, polyherbal Unani formulation, protects liver and antioxidative enzymes against paracetamol induced hepatotoxicity

Abstract: Context: Habb-e-Asgand, a polyherbal Homeopathy/Unani drug from Hamdard Wakf Laboratory, India, used in arthritis, gout and joint pain, is a mixture of many herbal medicinal plants. Scientific attempts to test and validate its efficacy are meager. Objective: To evaluate the hepatoprotective and antioxidative potential of Habb-e-Asgand against paracetamol toxicity. Materials and methods: Swiss albino male mice (n = 5/group) were treated with Habb-e-Asgand (250 mg/kg, body weight (b.w.) in normal saline orally f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Since oxidative stress seems to be involved in many diseases, the administration of anti-oxidants may be useful in the prevention and treatment of these diseases (Sekler et al, 2008). Currently, there is an increasing interest in naturally derived bioactive compounds with potential cytoprotective effects against oxidative stress induced cell death (Ali et al, 2014;Jaydeokar et al, 2014). Lepidium sativum has been widely used to treat a number of diseases in conventional medical system.…”
Section: Discussionmentioning
confidence: 99%
“…Since oxidative stress seems to be involved in many diseases, the administration of anti-oxidants may be useful in the prevention and treatment of these diseases (Sekler et al, 2008). Currently, there is an increasing interest in naturally derived bioactive compounds with potential cytoprotective effects against oxidative stress induced cell death (Ali et al, 2014;Jaydeokar et al, 2014). Lepidium sativum has been widely used to treat a number of diseases in conventional medical system.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 and Figure 2 illustrate the hepatotoxins utilised in the experiments to induce liver dysfunction in animal models, as well as the frequency with which each hepatotoxin was used. They include CCl 4 (Ahmad et al 2020;Arsul, Wagh & Mayee 2011;Balkrishna, Lochab & Varshney 2022;Bera et al 2012;Gurusamy et al 2010;Nipanikar, Chitlange & Nagore 2017;Said et al 2022;Sarhadynejad et al 2016;Yogi & Mishra 2017), thioacetamide (Balkrishna et al 2022), hydrogen peroxide (H 2 O 2 ) (Ndefo et al 2021), gentamicin (Aziz et al 2017), methotrexate (MTX) (Anila et al 2015), cadmium chloride (CdCl 2 ) (Singh et al 2023), D-galactosamine (Khan et al 2015;Sachdeva, Bajpai & Razdan 2013;Shetty et al 2020), alcohol (Dey et al 2020;Kanchana & Jayapriya 2013;Nipanikar et al 2017;Rafi Reshi et al 2022;Shetty et al 2018), cisplatin , isoniazid (INH) (Sankar, Rajkumar & Sridhar 2015), acetaminophen (Ali et al 2014;Fiaz et al 2017;Gupta et al 2013;Mayuren et al 2010;Nipanikar et al 2017;Patel et al 2013;Ray, Taraphdar & Gupta 2022;Saroj, Mani & Mishra 2012;Sen et al 2015;Shakya 2011;Shrivastava & Garg 2015;…”
Section: Review Findings and Discussionmentioning
confidence: 99%
“…One study found that Habb-e-Asgand exhibited significant antioxidative potential against paracetamol toxicity by increasing the activity of antioxidant enzymes such as glutathione reductase, glutathione peroxidase, glutathione S-tranferase, catalase, and glutathione contents. 61 Similarly, another study showed that rats treated with isoniazid and rifampicin experienced severe oxidative stress-induced lipid peroxidation, but supplementation with heptoplus and Liv 52 prevented oxidative damage and restored normal serum liver biochemical markers. 62 In addition, several polyherbal formulations, such as Livergen, PNK, Karisalai Karpam, and HP-4, were found to exhibit significant antioxidant activity by increasing the levels of various antioxidant enzymes and reducing the levels of TBARS, which is a marker of oxidative insult.…”
Section: Antioxidant Activity Of Polyherbal Formulationsmentioning
confidence: 98%